2020
DOI: 10.5888/pcd17.200049
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Interventions to Increase Colorectal Cancer Screening Among American Indians and Alaska Natives

Abstract: What is already known about this topic? Reducing client and structural barriers can result in greater participation in colorectal cancer screening, when stool-based tests are used. What is added by this report? Direct mailing of fecal immunochemical test kits was an effective strategy to increase colorectal cancer screening participation at rural, tribally operated health care facilities. What are the implications for public health practice? Stool-based testing is often the most accessible colorectal cancer sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Similarities were also found between our results and that of other cancers such as breast cancer in other AI communities [ 41 ]. This similarity finding may mean that other AI communities’ or regions’ colorectal cancer prevention efforts may have applicability in tribal communities in North Dakota [ 42 44 ]. Appropriate local adaptations will still likely be needed due to important cultural nuances.…”
Section: Discussion: Engaging With and Elevating American Indian Voicesmentioning
confidence: 97%
“…Similarities were also found between our results and that of other cancers such as breast cancer in other AI communities [ 41 ]. This similarity finding may mean that other AI communities’ or regions’ colorectal cancer prevention efforts may have applicability in tribal communities in North Dakota [ 42 44 ]. Appropriate local adaptations will still likely be needed due to important cultural nuances.…”
Section: Discussion: Engaging With and Elevating American Indian Voicesmentioning
confidence: 97%
“…19 Other collaborations with tribal organizations in Alaska, Minnesota, Arizona, New Mexico, and various health facilities in the Northern Plains have also been established to improve colorectal cancer screening, implement Cancer April 15, 2022 screening navigator services, and develop patient educational resources to increase awareness of colorectal cancer screening. [20][21][22] The CDC has also funded organizations such as the American Indian Cancer Foundation (AICAF) to support Urban Indian Health Programs nationally through screening, navigation, and evidence-based interventions (EBIs). 23 These EBIs have been centrally focused on 5 specific topics-human papillomavirus, colorectal cancer, hepatitis C, tobacco cessation, and survivorship.…”
Section: Discussionmentioning
confidence: 99%
“…The CDC's National Breast and Cervical Cancer Early Detection Program provides breast cancer screening for 33% of eligible AI/AN women 19 . Other collaborations with tribal organizations in Alaska, Minnesota, Arizona, New Mexico, and various health facilities in the Northern Plains have also been established to improve colorectal cancer screening, implement screening navigator services, and develop patient educational resources to increase awareness of colorectal cancer screening 20‐22 …”
Section: Discussionmentioning
confidence: 99%
“…Some have reported that Black persons were less likely than White persons to receive surgical treatment and adjuvant chemotherapy [ 39 – 42 ]. Differences in posttreatment surveillance and comorbidities among AIAN and NHB persons may also influence survival disparities [ 6 , 36 ]. That AIAN persons’ cause-specific survival probabilities decrease faster than all other races for localized-stage CCs over five years suggests suboptimal CC treatment relative to that of non-AIAN persons: the average per capita healthcare expenditures for the IHS population were $4078 in 2019, less than half the corresponding expenditures for the general US population [ 43 ].…”
Section: Discussionmentioning
confidence: 99%